ANALISIS KESESUAIAN MANAJEMEN PENGELOLAAN LOGISTIK OBAT DI INSTALASI FARMASI RUMAH SAKIT ISLAM PURWOKERTO TAHUN 2024 - M.Farm, Siti Asadu Sofiah; Sari, Ayu Nawang; Adelia, Desy Arisandi (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Drug management is an important element in pharmacy management that includes selection, planning, procurement, receipt, storage, distribution, disposal, control, recording, and reporting. This research aimed to analyze the suitability of drug logistics management in the pharmacy installation of Rumah Sakit Islam Hospital Purwokerto according to Permenkes Number 72 of 2016. A descriptive qualitative with data collection through interviews, checklists, and observations from informants such as the head of IFRS, coordinators, and TTK was used as a method in this research. The results showed that in terms of input, human resources reached 100%, while facilities and infrastructure were 75%. Several aspects need evaluation, such as logistics management training and additional storage space. The selection, planning, and distribution processes all reached 100%. However, procurement was only 80% due to the use of manual systems and e-catalogs that have not been fully implemented. Drug receipt reached 50% and storage 73.6%, where inadequate storage space caused accumulation. From those findings, there needs to be an improvement in the temperature recording system and labeling of high-alert drugs and LASA. In overall output, drug logistics management at Rumah Sakit Islam Hospital Purwokerto has met the criteria of good with 100% conformity, indicating effectiveness in drug management.